A preferred reality: Film portrayals of robots and AI in popular science fiction. Issue 1 (1st April 2021) - Dieter, Daniel G.; Gessler, Elyse C.
The increasing frequency and depth of human interaction with robots and artificial intelligence (AI) prompts this research study into how media-framed portrayals of technology in popular visual media might construct social reality. Cinema serves as an important and influential form of media, and portrayals of technology in film media can influence public perceptions, specifically confirming or creating perceptions of artificial or robotic intelligence. Previous research identifies frequent portrayals of robots and AI as deceptive, aggressive monsters in films like Fritz Lang's Metropolis and James Cameron's The Terminator. However, as the distance between fantastic technology collapses into a new social reality where humans, AI and robots exist together, film portrayals reflect a more nuanced view and changing expectations for human-robot, human-AI interactions. The study applies framing theory and a content analysis methodology to examine filmmakers' choices to determine robot and AI character types frequenting popular cinema. Seventeen popular films yielded 592 scenes to analyse. Findings from this quantitative content analysis revealed patterns portraying robots and AI more often as friendly, helpful companions of humans, rather than menacing or harmful to humans. Therefore, the researchers conclude that modern films primarily depict cohesive and complimentary interactions between humans and living technology, reflecting on heavy technology use and dependency. Furthermore, individuals who create these films may be illustrating scenes of a preferred reality, where AI and robots are meant to be our helpers, rather than threatening replacements in both society and industry.